Evolutions of upwelling and terrestrial organic matter input in the inner shelf of the East China Sea in the last millennium revealed by long-chain alkyl diols proxies - Chuanhui Song; Tianxiang Dang; Ting Zhang; Tiantian Ge; Rong Xiang; Lei Xing; Rui Bao; Yang Zhou; Rui Xiao; Baojin Wu (Frontiers in Marine Science, 2022)
Long-chain alkyl diols (LCDs) can be used as organic geochemical proxies for paleoceanographic change, especially in marginal sea areas where large volumes of sediments are deposited rapidly and continuously. However, little is known about the applicability and response on a millennium scale in relation with existing records in those sediments. We reconstruct changes in upwelling and terrestrial organic matter (OM) input in core sediments from the Zhejiang Fujian coastal station (T08) and Yangtze River Estuary station (T06) in the inner shelf of the East China Sea (ECS) over the last millennium, using the LCD based proxies: diol index 2 (DI-2), and FC 32 1,15-diol. Our results show that DI-2 values ([(C 28 +C 30 )1,14-diols]/([(C 28 +C 30 )1,13-diols]+[(C 28 +C 30 )1,14-diols])) at T08 decrease significantly during 600–400 yr BP but increase gradually after 400 yr BP. The FC 32 1,15-diol proxy ([C 32 1,15-diol]×100/([(C 28 +C 30 )1,13-diols]+[(C 30 +C 32 )1,15-diols])) at T06 shows marked fluctuations during 1000–800 yr BP, followed by a significant decline during 800–500 yr BP but a subsequent increase from 500 to 300 yr BP. We find that variations in DI-2 values are broadly consistent with changes in the strength of the East Asian Summer Monsoon (EASM) and the Kuroshio Current and are likely linked to changes in the frequency and intensity of the El Niño-Southern Oscillation (ENSO). The increased strength of the EASM causes greater offshore movement of the upper layer of seawater, which in turn triggers upwelling of bottom waters formed by Kuroshio subsurface waters. We find that variations in FC 32 1,15-diol proxy are controlled mainly by the East Asian Winter Monsoon (EAWM) and the Yangtze River discharge. By increasing the strength of the EAWM, southward transportation of material deposited in the estuary of the Yangtze River by the ECS coastal currents is promoted. In addition, we synthesize records of other organic geochemical indicators nearby core sediments in the ECS; these records emphasize the importance of reconstructing the evolutionary history of upwelling and subdividing the relative inputs of terrestrial OM. Our study provides a new means for reconstructing the evolution of upwelling and terrestrial OM input in the inner shelf of the ECS over the last millennium.